Self-assembly of hydrophobin and hydrophobin/surfactant mixtures in aqueous solution. - Zhang, X; Penfold, J; Thomas, R; Tucker, I; Petkov, J; Bent, J; Cox, A; Grillo, I (2011)
The self-assembly of the protein hydrophobin, HFBII, and its self-assembly with cationic, anionic, and nonionic surfactants hexadecylterimethyl ammonium bromide, CTAB, sodium dodecyl sulfate, SDS, and hexaethylene monododecyl ether, C(12)E(6), in aqueous solution have been studied by small-angle neutron scattering, SANS. HFBII self-assembles in solution as small globular aggregates, consistent with the formation of trimers or tetramers. Its self-assembly is not substantially affected by the pH or electrolytes. In the presence of CTAB, SDS, or C(12)E(6), HFBII/surfactant complexes are formed. The structure of the HFBII/surfactant complexes has been identified using contrast variation and is in the form of HFBII molecules bound to the outer surface of globular surfactant micelles. The binding of HFBII decreases the surfactant micelle aggregation number for increasing HFBII concentration in solution, and the number of hydrophobin molecules bound/micelle increases.